Filologia română la Universitatea din Cernăuți: dialoguri interculturale - Vranceanu, Felicia (Institutul European, 2022)
Bucovina is a land where, for centuries, different ethnic groups have coexisted. Undoubtedly, the issue of multiculturalism was one of the topics frequently addressed by those interested in the socio-political changes that took place for centuries, but the foundation of a higher education institution in Chernivtsi in 1875 meant a systematization of concerns for dialogues intra- and intercultural. At the same time, the Department of Romanian language and literature of the University of Chernivtsi was a center of pondering over the problem of balance between national identity and cultural diversity. What propelled the Romanian philology from Chernivtsi as value was the presence in the capital of Bukovina of some illustrious scholars, who became the foundation of cultural life in this land. Ion Gheorghe Sbiera, Sextil Pușcariu, Alexe Procopovici, Leca Morariu, Sever Pop are just some of the scholars who, at the end of the 19th century and in the first half of the 20th century, established and consolidated an academic tradition within the Department of Romanian Language and Literature of the University of Chernivtsi. The department will change its name over time, but what will be maintained will be the desire to preserve the identity profile of Romanian culture. Concerns for the study of intercultural dialogue have always been an important component of the activity of Bucovina researchers, among them the illustrious members of the Romanian language and literature department. Those who lived and worked in the multiethnic spaces were aware of the importance of finding solutions that would ensure, on the one hand, the necessary degree of linguistic mobility of people belonging to various cohabiting ethnic groups and, on the other hand, maintaining and asserting their own linguistic identities.
Keywords: intercultural communication; multiculturalism; multiethnicity; national culture; mother tongue